Estratégias preventivas de eventos adversos com medicamentos potencialmente perigosos em hospitais: uma revisão de escopo - Santos, Geovana Oliveira Anschau dos (2024)
Potentially Hazardous Medications, also known as high-alert medications, are considered to have an increased risk of causing significant harm to patients through adverse events. The multidisciplinary healthcare team plays a substantial role in risk management and the development of effective strategies to prevent these adverse events. Objective: To map the scientific production on the use of strategies to prevent adverse events with Potentially Hazardous Medications by multidisciplinary teams in hospitals. Method: This is a Scoping Review guided by the recommendations of the Joanna Briggs Institute and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. Searches were conducted from November 2023 to January 2024 in the following databases: Cumulative Index to Nursing and Allied Health Literature; Latin American and Caribbean Health Sciences Literature; PubMed/Medline; Scopus. Grey literature included the analysis of dissertations and theses published in the Capes Theses and Dissertations Portal and EBSCO Open Dissertations. Results: Initially, a total of 1,687 studies were identified, but only 14 studies were included in the review. After reading and extracting data, contents were grouped based on their similarities and differences, resulting in three categories: Potentially Hazardous Medications risk management; Healthcare professionals' knowledge deficit about Potentially Hazardous Medications; Strategies in preventing adverse events with Potentially Hazardous Medications. Conclusion: This scoping review mapped the use of preventive strategies for adverse events with Potentially Hazardous Medications by multidisciplinary teams in hospitals. In summary, the reviewed studies indicate that a multifaceted approach involving pharmaceutical intervention, patient safety committees, the use of technologies, standardized classification, the establishment of barriers and alerts, and continuous professional training are the most effective strategies in preventing adverse events related to Potentially Hazardous Medications.